Chinese commemorative practices in an English graveyard – observations on the Elswick gravestones - Bruce Davenport; Yuan Zhang; Andrew Law (Built Heritage)
Abstract This paper explores the contemporary use, for commemorative purposes, of Chinese heritage situated outside of China, in the built environment of Newcastle-upon-Tyne (United Kingdom). The focus of the paper is the recent history of five gravestones of Chinese sailors who came to Newcastle in the 1880s as part of a delegation to receive cruisers that had been designed and built for the Qing Dynasty’s Beiyang Fleet. The restoration of the gravestone in 2016–19 situated the gravestones as historic artefacts marking the birth of the Beiyang Fleet. Drawing on material evidence of recent commemorative reuse of the gravestones by contemporary Chinese subjects, the paper considers their on-going role in fostering national identities. Particularly, this paper acknowledges the role of these gravestones in broader discursive national narratives of humiliation and rejuvenation. The objects and messages deposited at the gravestones are interpreted in the light of historic Chinese commemorative practices and tensions surrounding them. The evidence indicates that visitors are reconfiguring the deceased sailors as ancestors/founders of the modern Chinese Navy.